Comparative evaluation of 2D and 3D YouTube videos as supplementary educational resources for vitreoretinal surgery training - Yozgat, Zubeyir; Sahin, Halime Kubra; Dumlupinar, Gizem Ilayda; Sabaner, Mehmet Cem (Ovid Technologies (Wolters Kluwer Health), 2024)
Ophthalmologists and ophthalmology residents (ORs) are increasingly turning to the internet for medical information, underscoring the significant role that YouTube videos, particularly three-dimensional (3D) ones, play in lifelong learning. This study aimed to compare the content and quality of 3D YouTube videos with two-dimensional (2D) videos as supplementary educational tools for vitreoretinal surgery. Data collected included video length (minutes), time elapsed since upload (days), number of views, likes, dislikes, vitreoretinal surgery type, and visualization system. Video popularity and interaction were calculated using the video power index, interaction index, and viewing rate. Two senior ophthalmologists (SOs) and 2 ORs evaluated the videos using the DISCERN, Global Quality Score, and usefulness scoring systems. Inter-rater reliability was assessed using the intra-class correlation coefficient. A total of 392 videos were screened, with 67 2D and 67 3D videos deemed appropriate for inclusion. While 2D videos had significantly more views, likes, interaction index, and viewing rate than 3D videos (P < .001 for all), 3D videos were rated higher by ORs across all scoring systems (P < .05 for all). Inter-rater reliability was confirmed to be good, with the lowest intra-class correlation coefficient being 0.796 for SOs (95% confidence interval: 0.668–0.875) and 0.814 for ORs (95% confidence interval: 0.698–0.886). In conclusion, side-by-side 3D YouTube videos offer a valuable supplementary educational tool, enhancing depth perception and enabling both SOs and ORs to better understand the complexities of ocular surgeries, particularly vitreoretinal procedures. These videos can also be used to observe new procedures and refresh previously acquired knowledge of past surgeries.
Keywords: Ophthalmology; Video Recording; Humans; Internship and Residency; Reproducibility of Results; Vitreoretinal Surgery; Social Media